COMBINED 24-HOURS ESOPHAGEAL PH MONITORING AND MULTICHANNEL INTRALUMINAL IMPEDANCE FOR COMPARISON OF GASTROESOPHAGEAL REFLUX IN CHILDREN WITH TYPICAL VERSUS ATYPICAL SYMPTOMS OF GASTROESOPHAGEAL REFLUX DISEASE - DEHGHANI,Seyed Mohsen (2016)
ABSTRACT Background - Gastroesophageal reflux disease is the most common esophageal disorder in pediatrics. Objective - The aim of this study was to compare reflux parameters of typical and atypical symptoms of gastroesophageal reflux disease using 24-hour esophageal pH monitoring and multichannel intraluminal impedance in pediatric population. Methods - In this prospective study, 43 patients aged less than 18 year with suspected gastroesophageal reflux disease were enrolled. The patients were divided into two groups based on the main presenting symptoms (typical versus atypical). Twenty four-hour pH monitoring and multichannel intraluminal impedance were performed in all the patients for comparing these two group regarding association of symptoms and reflux. Number of refluxes, pH related reflux, total reflux time, reflux more than 5 minutes, longest time of the reflux, lowest pH at reflux, reflux index were recorded and compared. Data comparison was done using SPSS. Results - The mean age of the patients was 5.7±3.4 years and 65.1% were male. Out of 43 patients 24 cases had typical symptoms and 19 had atypical symptoms. The mean reflux events detected by multichannel intraluminal impedance was more than mean reflux events detected by pH monitoring (308.4±115.8 vs 69.7±66.6) with P value of 0.037, which is statistically significant. The mean symptom index and symptom association probability were 35.01% ± 20.78% and 86.42% ± 25.79%, respectively in multichannel intraluminal impedance versus 12.73% ± 12.48% and 45.16% ± 42.29% in pH monitoring (P value <0.001). Number of acid reflux was 46.26±47.16 and 30.9±22.09 for atypical and typical symptoms respectively. The mean symptom index was 18.12% ± 13.101% and 8.30% ± 10.301% in atypical and typical symptoms respectively (P=0.034). Bolus clearance was longer in atypical symptoms compared typical symptoms(P<0.05). Conclusion - Symptom index was significantly higher in atypical symptoms compared to typical symptoms. Higher number of acid reflux was found in children with atypical symptoms of reflux. Longer duration of bolus clearance was found in group with atypical symptoms of reflux.